Islam dan Kekerasan Dalam Rumah Tangga (Kajian Tafsir Hukum QS. Al-Nisa/4: 34) - Sakirman Sakirman (Al-Mizan, 2015)
Domestic violence is a huge problem and it needs serious handling, both countries through product of laws or religion through the messages of the Qur’an and hadith. This paper discusses the study of interpretation of surah al-Nisā’/4: 34 with a normative approach and it is analyzed by the method of contextual. The results show Islam is a religion that it does not require the existence of discrimination that gave birth to violence, particularly in the domestic sphere. Although in the study of the interpretation of surah al-Nisā’/4: 34 provides justification for the husband beating, but the verse is interpreted by contemporary scholars and it need to reinterpretation and other meaning of words (takwil) in the verse.